Determination of Optimal Non-Denaturing Elution Conditions from Affinity Columns by a Solid-Phase Screen. (September 2001) - Fuchs, Hendrik; Tauber, Rudolf; Geßner, Reinhard
The purification of biological macromolecules by affinity chromatography is a widespread technique used to separate a protein from other biological components. However, this method may destroy the protein's physiological activity because elution conditions aimed to dissociate the protein of interest from the high-affinity matrix often irreversibly denature it. In the present work, we have developed a solid-phase assay to determine the optimal elution conditions for any buffer (in two steps) by determining (i) the lowest buffer concentration yielding maximum dissociation from the immobilized component and (ii) the highest buffer concentration that can be used without the loss of the protein's binding activity. Any buffer that can be reasonably used between these defined concentrations is suitable for elution within this interval. The screen is easily performed within a few hours and only requires nanograms to a few micrograms of protein. As an example, we demonstrate that more than 95% of the human transferrin receptor bound to a transferrin-sepharose ligand affinity column can be eluted with full binding activity at KSCN concentrations between 232 and 414 nM, whereas elution with urea is not suitable to purify fully functional protein.